Gemcitabine and docetaxel for high-risk non-muscle-invasive bladder cancer: EuroGemDoce group results - Scilipoti, Pietro; Longoni, Mattia; de Angelis, Mario; Zaurito, Paolo; Massiet, Albane; Dutto, Daniele; Soria, Francesco; Álvarez-Maestro, Mario; Bazán, Alfredo Aguilera; Pradere, Benjamin; Klatte, Tobias; Contieri, Roberto; et al. (BJU international, 2025)
OBJECTIVE: To evaluate the oncological efficacy and safety of sequential intravesical gemcitabine/docetaxel (Gem/Doce) therapy in a European cohort of patients with high-risk and very-high-risk non-muscle-invasive bladder cancer (NMIBC) after previous Bacillus Calmette-Guérin (BCG) treatment. MATERIALS AND METHODS: Data were retrospectively collected from 95 patients with NMIBC, treated with Gem/Doce at 12 European centres between 2021 and 2024. Patients previously treated with BCG who had completed a full induction course and received at least one follow-up evaluation were included. One-year disease-free survival (DFS), high-grade DFS and progression-free survival (PFS) were estimated using Kaplan-Meier curves. Adverse events (AEs) were recorded through medical interviews. RESULTS: Of 75 patients, 63 (84%) were classified as having high-risk and 12 (16%) as having very-high-risk NMIBC. Over a median (interquartile range) follow-up of 9 (5-14) months, 20 patients (27%) relapsed and five (6.7%) underwent radical cystectomy. The 1-year DFS was 73% (95% confidence interval [CI] 62-86%), 1-year high-grade DFS was 79% (95% CI 68-91%) and 1-year PFS was 95% (95% CI 90-100%). AEs occurred in 34 patients (45%), with six (8.7%) experiencing severe AEs. Limitations of the study include the short follow-up and variability in both treatment dwelling times and dosage across centres. CONCLUSION: The intravesical Gem/Doce regimen demonstrated promising short-term oncological outcomes and was well tolerated in this cohort of patients with high- and very-high-risk NMIBC previously treated with BCG. Prospective studies and randomised trials are awaited to define the ideal candidates for Gem/Doce therapy and to standardise treatment protocols.
Keywords: Administration, Intravesical; deoxycytidin; gemcitabine; docetaxel; Europe; senioři; Aged; Male; Retrospective Studies; lidé; invazivní růst nádoru; oncological outcomes; Urinary Bladder Neoplasms; lidé středního věku; Humans; Antineoplastic Combined Chemotherapy Protocols; Docetaxel; retrospektivní studie; Evropa; Middle Aged; nádory močového měchýře neinvadující svalovinu; gemcitabin; Neoplasm Invasiveness; Non-Muscle Invasive Bladder Neoplasms; aplikace intravezikální; protokoly protinádorové kombinované chemoterapie; BCG Vaccine; adverse events; Gemcitabine; mužské pohlaví; nádory močového měchýře; ženské pohlaví; Deoxycytidine; Female; non‐muscle‐invasive bladder cancer; BCG vakcína